Nanoarchitectonics for Advancing Bone Graft Technology: Integration of Silver Nanoparticles Against Bacteria and Fungi - Leticia Ramos Dantas; Maria Alice Witt; Everdan Carneiro; Felipe Francisco Tuon (Microorganisms)
Silver nanoparticles have garnered significant attention for their antimicrobial applications. The aim of this study was to develop and characterize a silver nanoparticle-enhanced bone graft and assess its antimicrobial and antibiofilm activities. Bone granules from bovine cancellous femur were impregnated with silver nanoparticles (50 nm). The antimicrobial and antibiofilm activity was tested against various pathogens, including Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, Enterococcus faecalis, Acinetobacter baumannii, and Escherichia coli. Biocompatibility and resorption were evaluated in a mouse calvaria model. All the tested pathogens showed susceptibility to silver nanoparticles, with minimal inhibitory concentrations ranging from 0.25 to 4 mg/L. The silver nanoparticle scaffolds demonstrated a significant reduction in biofilm formation across all microorganisms. The graft exhibited a biocompatibility comparable to that of autologous bone, with reduced resorption rates. Additionally, the presence of nanoparticles did not impact radiolucency, and cytotoxicity remained minimal. Bone grafts impregnated with silver nanoparticles effectively reduce biofilm formation, suggesting their potential as a strategic material for various implant applications.